Penguatan Pengembangan Wisata Tangkahan Kabupaten Langkat Melalui Brand Tourism Berbasis Social Media - Adhani, Abrar; Hamzah Lubis, Faizal; Hardiyanto, Sigit (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2021)
The goal to be achieved in this community service program is to help tourism managers as well as the people of Namo Sialang Village, Langkat Regency to develop, increase motivation and ability in the field of social media-based promotion by creating attractive advertising design content using applications on smartphones. Based on the results of the implementation of community service carried out, the socialization of activity programs by the service team can be explained about how strategies in developing Tangkahan tourism in Langkat Regency through brand tourism, strengthening institutions for tourism managers who are also people of Namo Sialang Village and making attractive designs and content based on social media which can provide opportunities in developing tourism Tangkahan Langkat Regency. From community service activities regarding strengthening the tourism development of Tangkahan in Langkat Regency through social media-based tourism brands, it can contribute to the community such as developing information such as social media-based tourism development strategies, creating interesting content and strengthening institutions for tourism managers.Keywords: Community Empowerment, Tourism Development, and Social Media